The Comparative of Life Cycle Assessments Between Steel and Reinforced Concrete Structures - GHREIWATI, FAWZI (İstanbul Kültür Üniversitesi, 2022)
The major of this study is to understand the influence of considering the lateral load during the design face of the buildings on the 𝐶𝑂2 emissions. Since steel and reinforced concrete structures have been used in a variety of buildings in the United States in recent years, it is critical to examine and perform research on the environmental implications of the designs and materials used in those constructions. This study investigated various multi-story residential structures in the United States with similar functions for this purpose. sixteen of the buildings was constructed with a steel frame and the other thirteen with a concrete structure. Accordingly, to achieve these aims assets of 32 different structures vary considering factors such as structural type, height, location of the structure, and loading scenarios. As this study show that Concrete structures emitted 23% more CO2 than steel buildings. While the results reveal that constructing a concrete building in an A class earthquake area creates 25% higher CO2 emissions than building in a non-seismic region.
Çelik ve Betonarme Yapılar Arasındaki Yaşam Döngü Değerlendirmelerinin Karşılaştırılması
▪ Yüksek lisans tezi.
Keywords: LCA; Carbon footprint; Athena Impact Estimator for Buildings; Steel Building; Reinforcement building; Earthquake Resistant Design